Extreme Ultraviolet Lighting Using Carbon Nanotube-Based Cold Cathode Electron Beam - Sung Tae Yoo; Kyu Chang Park (Nanomaterials, 2022)
Laser-based plasma studies that apply photons to extreme ultraviolet (EUV) generation are actively being conducted, and studies by direct electron irradiation on Sn for EUV lighting have rarely been attempted. Here, we demonstrate a novel method of EUV generation by irradiating Sn with electrons emitted from a carbon nanotube (CNT)-based cold cathode electron beam (C-beam). Unlike a single laser source, electrons emitted from about 12,700 CNT emitters irradiated the Sn surface to generate EUV and control its intensity. EUV light generated by direct irradiation of electrons was verified using a photodiode equipped with a 150 nm thick Zr filter and patterning of polymethyl methacrylate (PMMA) photoresist. EUV generated with an input power of 6 W is sufficient to react the PMMA with exposure of 30 s. EUV intensity changes according to the anode voltage, current, and electron incident angle. The area reaching the Sn and penetration depth of electrons are easily adjusted. This method could be the cornerstone for advanced lithography for semiconductor fabrication and high-resolution photonics.